PENGEMBANGAN HANDOUT BERGAMBAR YANG DISERTAI PETA KONSEP PADA MATERI STRUKTUR DAN FUNGSI SEL SEBAGAI UNIT TERKECIL KEHIDUPAN UNTUK SMA/MA - Maiasputri, Nike - (STKIP PGRI Sumbar, 2014)
Biology instructional materials used by students of SMAN 11 Padang is textbook and worksheets. The use of textbooks that is optimal to assist students in learning, because textbooks are loaned from the school library can only be used in the learning process time at school. As a result, the students find difficulties to repeat the lesson. In addition, text books and worksheets that are used have a simple display, the images present in black and white, images and descriptions are less clear, material explanation of the teaching material is quite concise. Thus, the students are less motivated to read teaching materials and being about the task of teachers. In studying the structure and function of cell material as the smallest unit of life, the learning needs pictures that can help the students to understand the learning material for the image and structure of cell organelles can not be seen directly. To assist students in the learning process, the teacher develops teaching materials in the form of handouts. This study aims to determine the validity and handouts that accompanied the practicalities of a concept map on the material structure and function of the cell as the smallest unit of life for SMA/MA. This research is the development of the use of 4-D Models consists of 4 stages namely, define, design, develop and disseminate, but this study is limited to develop stage (development). This type of research data is the primary data which consist of the results of the validity and practicalities. This study was conducted on May 20, 2014 in SMAN 11 Padang. Validity test results illustrated handout accompanied by a concept map validator indicated that this handout was very valid criteria with an average value of 94.29%. Test results illustrated handouts that accompanied the practicalities of concept maps by the teacher indicated that this handout was a very practical criterion is 92.76% and test the practicalities of the students indicated that this handout was very practical criteria with an average value of 95.49%. It were be concluded that the handouts that accompanied the pictorial concept map produced very valid and very practical.